Validity of the Psychological Well-Being Scale with Morbid Female Obesity - Aparecida Medeiro, Sandra (2022)
Psychological well-being is an important indicator of psychological adjustment. Obesity is considered a progressive disease that results in serious public health problems. This investigation sought validity evidence for the Psychological Well-Being Scale in 293 morbidly obese Brazilian women, aged between 18 and 61 years, who were awaiting bariatric surgery. The scores were submitted to Confirmatory Factor Analysis and several theoretical models were tested. According to the results, an oblique six-dimensional structure presented a good fit to the empirical data. Acceptable indices of internal consistency for the measurement factors were also obtained. The scale may contribute to the development of programs aimed at improving the psychological well-being of people with morbid obesity, before and after bariatric surgery.